Sleep positioning systems for children and adults with a neurodisability: A systematic review. (January 2019) - Humphreys, Ginny; King, Tanya; Jex, Jo; Rogers, Morwenna; Blake, Sharon; Thompson-Coon, Jo; Morris, Christopher
Introduction: Sleep positioning systems are often prescribed as part of a 24-hour postural management programme for children and adults with neurodisabilities. In a search for evidence of effectiveness for children with cerebral palsy a recent Cochrane review found two randomised controlled trials. This review aims to appraise a broader set of studies including any neurological diagnosis and users of all ages to inform therapists about the quality of the evidence underlying practice. Method: A comprehensive search for all peer-reviewed studies that evaluated the use of sleep positioning systems was conducted in MEDLINE, EMBASE, CINAHL, Cochrane Library databases, BNI, HMIC, PEDro, OTSeeker and clinical trials registries. Disability organisations, manufacturers and colleagues worldwide were also contacted. Titles were screened for relevance by two reviewers. Data were extracted into bespoke quantitative or qualitative forms by one reviewer and checked by a second. Findings were analysed into simple themes. Results: A total of 14 studies were eligible for inclusion; all were small and most were of low quality. Inferences of benefits cannot be made from the literature but also no harm was found. Conclusions: The body of evidence supporting practice remains small and mostly of low quality. Therapists should remain cautious when presenting the benefits to families.